Chimeric antigen receptor T-cell therapy in relapsed or refractory mantle cell lymphoma: a systematic review and meta-analysis - Wan, Haixiang; Weng, Songqin; Sheng, Sumei; Kuang, Zilin; Wang, Qingming; Hu, Linhui (Frontiers in Immunology, 2024)
Background: Chimeric antigen receptor (CAR) T-cell therapy (CAR-T therapy) has demonstrated significant efficacy in the ZUMA-2 study. After regulatory approvals, several clinical trials and real-world studies on CAR-T therapy for relapsed or refractory mantle cell lymphoma (R/R MCL) were conducted. However, data on clinical safety and efficacy are inconsistent. In this study, we aimed to conduct a systematic analysis of the effectiveness and safety of CAR-T therapy across a wider and more representative cohort of patients with R/R MCL.We performed a systematic review and meta-analysis of studies on patients with R/R MCL who received CAR-T cell therapy. Data were extracted and consolidated, with primary focus on the evaluation of safety and efficacy outcome measures. This study has not been registered with PROSPERO.Results: This meta-analysis identified and included 16 studies with 984 patients. The pooled estimate for overall response rate (ORR) was 89%; complete remission (CR) rate was 74%. The 6-month and 12-month progression-free survival (PFS) rates were 69% and 53%, respectively, while the overall survival (OS) rates were 80% and 69%, respectively. Cytokine release syndrome (CRS) of grade 3 or higher was observed in 8% of patients, whereas neurotoxicity of grade 3 or higher was observed in 22% of patients.The risk of bias was assessed as low in 9 studies and moderate in 7 studies.CAR-T therapy exhibited promising efficacy and manageable adverse reactions in patients with R/R MCL.